2004
DOI: 10.1109/tec.2004.827026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Design Optimization of an Improved Axially Magnetized Tubular Permanent-Magnet Machine

Abstract: Abstract-This paper describes the analysis and design optimization of an improved axially magnetized tubular permanentmagnet machine. Compared with a conventional axially magnetized tubular machine, it has a higher specific force capability and requires less permanent-magnet material. The magnetic field distribution is established analytically in the cylindrical coordinate system, and the results are validated by finite-element analyses. The analytical field solution allows the analytical prediction of the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(46 citation statements)
references
References 14 publications
2
44
0
Order By: Relevance
“…The focus of these publications were generally of the torque-or total harmonic distortion (THD) measurements of the system [36][37][38][39] or its demagnetization behavior [32][33][34][35]. A number of studies have investigated linear machines with magnetization in the direction of motion [40][41][42][43][44]. Furthermore, modified pole shoes for a rotating PM synchronous wind turbine [45] and different salient pole shoe faces for a synchronous machine [46] were previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of these publications were generally of the torque-or total harmonic distortion (THD) measurements of the system [36][37][38][39] or its demagnetization behavior [32][33][34][35]. A number of studies have investigated linear machines with magnetization in the direction of motion [40][41][42][43][44]. Furthermore, modified pole shoes for a rotating PM synchronous wind turbine [45] and different salient pole shoe faces for a synchronous machine [46] were previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, various analytical models which used analytic field solution have been proposed. Some of them concern rotational electrical machines [6][7][8][9][10], and others linear machines [11][12]. An attractive motor design method and analysis is presented in [6] it is shown that the Halbach magnetized PMSM motor has 15% lower volume than the radial magnetized one.…”
Section: Introductionmentioning
confidence: 99%
“…However, the magnetization of a PM mover composed of AMPMs and iron poles cannot be modeled homogeneously [5], resulting in complicated boundary conditions in the z-direction [7]. These boundary conditions make it difficult to approach analytically.…”
Section: Introductionmentioning
confidence: 99%